Violence against Women: A Disciplinary Debate and Challenge. Issue 1 (January 2015) - Keating, Barbara
<x xml:space="preserve">Abstract</x> Forty years of research, theory, legislation, and programming have not reduced the high rates of either violence against women or intimate partner violence. Social science researchers, polarized into Family Violence and Feminist perspectives, are mired in the debate over gender symmetry and its implications. Recommendations include (1) integrating the two perspectives, (2) incorporating the work on family strengths, youth resilience and developmental assets, (3) strengthening interdisciplinary connections including religious studies, and (4) integrating research, teaching, and activism for long‐term, primary prevention. A three‐model typology of activism includes education, common cause, and confrontation strategies.